Synergistic interaction between quercetin and doxorubicin on MCF-7 human breast cancer cell line - Indwiani Astuti, Abdul Khairul Rizki Purba Mustofa (Universitas Gadjah Mada, 2013)
The effectiveness of doxorubicin has decreased due to resistance of cancer cells. One of thenatural ingredients that are proven to reduce the resistance to anticancer is quercetin. Quercetininteracts with doxorubicin via a competition of P-glycoprotein (P-gp) transporter activity. Theaim of this study is to evaluate the interaction of quercetin and doxorubicin as cytotoxicityeffect on MCF-7 cells. Cytotoxicity test was conducted by the MTT method. Mechanism ofinteraction between doxorubicin and quercetin was evaluated with isobologram analysis.Doxorubicin and quercetin inhibited the growth of MCF-7 cells significantly. Doxorubicin andquercetin respectively had IC50 of 21ïM and 103 ïM. The interaction of doxorubicin and quercetinwere characterized by the amount of doxorubicin IC50 equivalent and quercetin IC50 equivalentless than 1 and the point-intercept of each IC50 notation equivalent plotted on the graph belowthe additive line. Analysis of isobolograms indicated that the interaction doxorubisn and quercetinin each of the ratios had synergy. Quercetin can be considered to be in a combination wit